Toy preferences among 3-to-4-year-old children: The impact of socio-demographic factors and developmental characteristics - Nikolay N. Veresov; Margarita N. Gavrilova; Vera L. Sukhikh (Современное дошкольное образование)
Background. Today’s common typologies and categories of children’s toys are mainly decided by the manufacturers and retailers of children’s products. Such categorizations are not based on a theoretical understanding of child development and therefore cannot provide information about the opportunities that toys provide for the young.